Identifying growth criteria and sediment movement mechanisms of needle ice using high-frequency environmental and visual monitoring - Borg, Carl-Johan (Rhodes University, Faculty of Science, Department of Geography, 2017)
Environmental growth conditions and mechanisms involved in sediment transport by needle ice have historically been difficult to assess and are poorly documented. The spatial and temporal dynamics that relate to the environment, growth and decay of needle ice are not fully understood. This study monitored needle ice growth, melt and visually identified sediment displacement mechanisms by needle ice, with the aim of revealing environmental growth criteria, timing of growth/melt, ground-surface-air energy balance and sediment displacement mechanisms. Furthermore, the impact of needle ice displacement on vegetation and patterned ground formation was analysed. High-frequency visual monitoring, using three cameras, supplemented by high-frequency measurements of air temperature, soil moisture and wind speed was used to investigate needle ice growth and decay dynamics. Results from visual and environmental monitoring of needle ice growth, showed that the needle ice growing environment was more dynamic, especially in terms of surface temperature, than previously argued. Needle ice growth was observed to occur during surface temperatures from -2.0°C to 2.2°C, soil moisture levels from 0.4% to 37.4% and in winds speeds of 0 m/s to 12.6 m/s. Needle ice initiation was documented a few minutes to hours before or after the onset of surface temperature dropping to below 0°C. Imagery displayed that the depth of ice nucleation was variable within the soil column, possibly relating to the energy balance of radiative cooling, convective heat loss, ground conductivity and latent heat release at the air-surface-ground boundary. Heaving and resettling, toppling and rolling were identified as slope displacement mechanisms when needle ice decayed. Animal trampling and hail were additionally documented as substantial surface altering processes. Furthermore, no impact of needle ice reducing vegetation stability was identified, although a tendency to hinder vegetation expansion was noted. Also, no creation of patterned ground was observed as a result of needle ice decay.
Keywords: Frazil ice; Sediment transport; |ce mechanics; Photography -- Digital techniques; Environmental monitoring